An Analysis Upon the Role of Women In Agriculture Development: Women Empowerment In Agrarian Societies: Examining the Role of Women in Agricultural Development and Economic Empowerment (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Agriculture can be an important engine of growth andpoverty reduction. But the sector is underperforming in many countries in partbecause women, who are often a crucial resource in agriculture and the ruraleconomy, face constraints that reduce their productivity. In this paper we drawon the available empirical evidence to study in which areas and to what degreewomen participate in agriculture. The contribution of women to agricultural issignificant but it is impossible to verify empirically the share produced bywomen. Women’s participation in rural labour markets varies considerably acrossregions, but invariably women are over represented in unpaid, seasonal andpart-time work, and the available evidence suggests that women are often paidless than men, for the same work. In this study areamaximum no of women laborers are illiterate with no formal educational statuswhich directly informed their participation in agricultural production. Womenparticipation in rural labor markets varies considerably across regions, butinvariably women are over represented in unpaid, seasonal and part-time work,and the available evidence suggests that women are often paid less than men forthe same work. This paper re-affirms that women make essential contributions toagriculture and rural enterprises across the study area as well as developingworld.